EFFECTIVENESS OF INTERACTIVE DIGITAL STORYTELLING EDUCATION ON MENARCHE KNOWLEDGE AMONG EARLY ADOLESCENT GIRLS AT MI AL IRSYAD, KEDIRI, INDONESIA - Devy Putri Nursanti Devy; Eri Puji Kumalasari; Riza Tsalatsatul Mufida; Gufron Wahyudi (Universitas STRADA Indonesia, 2026)
Early menarche increases the risk of breast cancer, obesity, cardiovascular disease, metabolic disorders, and psychological problems. This study aimed to analyze the effect of interactive digital storytelling on menarche understanding among early adolescent girls at MI Al Irsyad, Kediri City. Using a pre-experimental one-group pretest–posttest design, 61 of 70 eligible students were selected by purposive sampling. Before the intervention, most respondents had poor understanding of menarche (57.4%, n = 35). After the intervention, almost all had good understanding (93.4%, n = 57). Cross-tabulation showed that many girls moved from poor to good categories, with 31 respondents (50.8%) improving from poor to good understanding. Paired t-test analysis showed a significant effect (p = 0.000 < 0.05), indicating that interactive digital storytelling effectively improved menarche understanding. This approach combines engaging narratives with interactive technology, providing a meaningful and non-intimidating learning experience for adolescents.